PERUBAHAN BENTUK BADAN HUKUM PERUSAHAAN UMUM MENJADI PERUSAHAAN PERSEROAN - Pratama, Bayu Hewu Pratama; Gindo L. Tobing; Thomas Abbon (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This thesis examines the legality and legal consequences of PT xxx's change in legal form from Perum to Persero, as regulated by PP No. 11 of 2020, in accordance with PP No. 43 of 2005 and Law No. 40 of 2007. Employing normative legal research with primary and secondary data, the study concludes that the change adheres to Articles 29-43 of PP No. 43 of 2005 and Law No. 40 of 2007. The legal consequences include the division of ownership into Series A Dwiwarna and Series B shares, and PT Jamkrindo (Persero) becoming subject to Law No. 40 of 2007 and Law No. 19 of 2003 concerning State-Owned Enterprises.